The Role of Self-Directed Learning in Older Adults’ Health Care - Janet S. Valente (Adult Education Research Conference, 2006)
This descriptive study expands the understanding of the impact of self-directed learning (SDL) on older adults’ health care. Findings reveal motivating and controlling factors that influence learners, identifies a SDL process specific to health care, offers insights into the perceptions older adults’ hold, and barriers they encounter.
Keywords: Self-directed learning; older adults; health care